2013
DOI: 10.3748/wjg.v19.i48.9410
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of type 2 diabetes mellitus after gastric cancer surgery: Short-term outcome analysis after gastrectomy

Abstract: Diabetes improved in more than 50% of patients during the first year after gastric cancer surgery. The degree of diabetes control was related to diabetes duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 10 publications
2
44
0
Order By: Relevance
“…We demonstrated that patients with long-term diabetes mellitus tended to have poor glycemic control after TP, and elderly patients might be subject to poor nutritional status. It is possible that insulin resistance is less severe in patients with a shorter duration of diabetes mellitus than in patients with a longer duration, as observed in gastrectomy[29]. On the other hand, functions of nutrient absorption and regulation are likely to diminish with previous alcohol history.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that patients with long-term diabetes mellitus tended to have poor glycemic control after TP, and elderly patients might be subject to poor nutritional status. It is possible that insulin resistance is less severe in patients with a shorter duration of diabetes mellitus than in patients with a longer duration, as observed in gastrectomy[29]. On the other hand, functions of nutrient absorption and regulation are likely to diminish with previous alcohol history.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oncologic benefits, gastrectomy can also contribute to the improvement of glucose metabolism or remission of diabetes mellitus (DM) [5][6][7][8]. Interestingly, 1 study emphasized that the extent of the gastrectomy plays an important role in DM improvement after curative surgery for GC (total gastrectomy [TG] versus subtotal gastrectomy: 81.8% versus 36.2%, respectively, P = .007) [9].…”
mentioning
confidence: 96%
“…Papers described as being of moderate quality failed to provide sufficient detail on the patients’ cancer such as type and stage [30,35], details of how patients were selected and why [35], how missing data was dealt with [30], or did not appropriately deal with confounding variables [31]. …”
Section: Resultsmentioning
confidence: 99%
“…Poorer adherence to diabetic medications post-cancer diagnosis was described in three studies and patients reported they either ceased taking DM medications [35], or reduced DM medications use after diagnosis [31,35]; and this supports findings from the study by Zanders and colleagues [21]. An explanation for this may be that little attention is paid to glycaemic control by cancer health professionals and/or poorer self-management by the patients themselves when also burdened with the added responsibilities and strains associated with other competing chronic conditions [30] including cancer self-management [13], however evidence to support this is extremely limited.…”
Section: Discussionmentioning
confidence: 99%